A projective study of the enrollment and financial status of Colegio de San Juan de Letran Calamba, Laguna 1982-1992 - Taclobos, Nelson (Animo Repository, 1984)
The major objective of this study is to determine and analyze the market viability of Letran Calamba within ten years and its financial standing for five years. As it is intended to be a blueprint for implementation, the research drew its hypotheses from varied sources which stress planning as pre-requisite for successful and effective management among educational institutions. For planning to be effective nowadays, moreover, it should be both projective and strategic. A wide range of factors must be considered most significantly those that have direct bearing on the immediate environment which in turn, are likely to influence the institution itself. Lately, national development goals have likewise been deemed to influence, to a large extent, the viability of the institution in terms of relevance to regional and national growth. Thus, a consideration of development goals was a significant aspect of this study. The complexity of the factors involved necessitated the use of a projective method in this study. It utilized the historical-analytical method in the analysis of data necessary for purposes of evaluation by interpretation. Research on Calamba town employed the Environmental Scanning Process of Franco, Soriano and Carino for the institutional audit, the historical-analytical method was used to which was added a survey questionnaire from which was drawn the socio-economic profile of students. Numerical data on enrollment also used the same research method with past enrollment records as basis for the computations to establish trends which will be used for planning. In this study, the enrollment data served as indirect determinants for projections in finances and human resources. From the same data likewise prospects or growth goals were established in terms of maximum capacity utilization, physical expansion, and implications to future research. The procedure for the analysis of data was undertaken along two different lines as presented in schematic diagram - the first was purely factual analysis of data gathered the second was an analysis of output in terms of strategic information - evaluated against the institution's strengths and weaknesses. Data were gathered for existing facts and documents for the environmental analysis, records of past enrollment, physical and manpower resources for the institutional audit which also included a survey questionnaire. Data on the environment presented and analyzed revealed both positive and negative points or as earlier pointed out, the risks and opportunities, among the positive points are: a high literacy rate in the region thus a big share in the educational population for Letran Calamba: the need for a well-rounded citizenry with solid humanist foundations in the region's development towards autonomy, an education which is characteristics of Letran the rapid development of the region as growth center to decongest Manila thus a positive development for Letran, likewise. Areas for Letran to improve on are the need for technological manpower and the demand for industrial expertise, both of which the institution is weak.